Mejora de los procesos comerciales para incrementar la participación de mercado en una empresa proveedora de la industria de la construcción - Baldeon Loyola, Aldo Jim (2024)
The Project promotes the profitable growth of Group Colombia, through the improvement of its business processes, based on engineering tools, as well as methodologies and systems to improve the efficiency of commercial team. First, the diagnosis showed a poor market understanding, besides market share results much lower than its counterparts, in markets also highly competitive. By having comparable figures from other countries, efficiency and growth targets can be set in the short, medium, and long term. Based on interviews to all commercial population, and a granular analysis of sales data, it was possible to elaborate a diagnosis, and identify the main causes that did not allow it to have the expected market share. Third, in a joint effort with commercial managers, objective criteria were determined to prioritize not only the business agenda, through selecting the most relevant projects, but the whole organization was aligned to deliver high service levels to the prioritized projects, the ones with the greatest future contribution. Finally, to give sustainability to the implemented definitions, as well as to ensure compliance with the long-term objectives, performance dialogues and routines are defined and structured within a methodological framework and are supported by an integrated platform of information facilitating monitoring and decision-making.